Game 3D MMORPG sebagai Media Pembelajaran Cerita Rakyat - Suardika, I Gede; ADH, IGKG Puritan Wijaya; Adnyana, I Made Budi (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
Folklore is a part of oral literature or a genre of folklore that has been told from generation to generation. Folklore can help in the process of forming a child's character which can influence academic success. It is very possible that folklore will be lost over time. Many things have been done in an effort to preserve folklore. Seeing the urgency of this problem, namely how important the benefits of folklore are and the preservation efforts that need to be made, this research tries to develop an MMORPG game technology that can be used as a medium for learning folklore. The research method used is Research and Development (R&D). This research has succeeded in developing an MMORPG game using the GDLC method where all the functionality contained in this game has been successfully executed according to expectations, tested using the Blacxbox Testing method using the State Transition technique. It is hoped that the quests or missions embedded in this game can become a medium for introducing and learning folklore in Indonesia.